Виховання іншомовної комунікативної культури студентів у закладах вищої освіти - Черничко Степан; Csernicskó István; Csernicsko Istvan; Берегсасі Аніко; Beregszászi Anikó; Aniko Beregszaszi; Чичук Антоніна; Chychuk Antonina; Csicsuk Antonina (Видавництво «Код», 2025)
Резюме. Соціокультурні трансформації, характерні для глобалізованого інформаційного простору, вимагають внесення змін у процес іншомовної освіти студентів як майбутніх фахівців. Передусім це стосується використання сучасних інформаційних технологій, які дозволяють створювати на заняттях інтерактивне мовне середовище та розширювати візуальний контент освітнього простору, ефективність яких у вивченні іноземної мови доказана світовим педагогічним досвідом. Розкрито чотири рівні сформованості іншомовної культури. Зміст іншомовної комунікативної культури включає соціальний, лінгвокраїнознавчий, психологічний і педагогічний аспекти. Саме тому для виховання іншомовної комунікативної культури особистості треба поетапно формувати глибокі, систематичні іншомовні знання, загальнолюдські цінності і поведінкові алгоритми.

Abstract. Modern global socio-political and economic changes arouse significant interest in the culture of other peoples as a determining condition for the realization of the creative potential of an individual and society as a whole. Recently, it is the foreign language that is considered a tool for the multicultural development of students’ personalities or a means of ensuring the integration of a person into a new society, into a new social situation. The carrier of the culture of the people and its most important national identifier is the language, which has a traditional character. Sociocultural transformations characteristic of the globalized information space require changes in the process of foreign language education of students as future specialists. First of all, this concerns the use of modern information technologies, which allow creating an interactive language environment in classes and expanding the visual content of the educational space, the effectiveness of which in learning a foreign language has been proven by world pedagogical experience. Foreign language communicative culture regulates communication between people in different cultural contexts. It is characterized by the presence of a communicative ideal, a tolerant attitude towards the interlocutor as a value, awareness of his individual characteristics, his own communicative abilities and the ability to master a communicative situation. This is a system of internal human resources necessary for existence in a range of situations of interpersonal interaction at different levels. Four levels of formation of foreign language culture are revealed. The content of foreign language communicative culture includes social, linguistic, regional, psychological and pedagogical aspects. That is why, in order to educate a foreign language communicative culture of an individual, it is necessary to gradually form deep, systematic foreign language knowledge, universal human values and behavioral algorithms.
Education of foreign language communicative culture of students in higher education institutions
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: іншомовна комунікативна культура; студенти; заклади вищої освіти; інформаційні ресурси; мультимедійні технології